Extending Business Process Models with Appreciation - Rychkova, Irina; Regev, Gil; Wegmann, Alain (Complex Systems Informatics and Modeling Quarterly, 2019)
We use homeostasis, the maintenance of steady states in an organism, to explain some of the decisions made by participants in a business process. We use Vickers’ Appreciative System to model the homeostatic states with Harel’s statecharts. We take the example of a doctoral student recruitment process formally defined between a faculty member, a graduate student candidate and a doctoral school. We analyze some gaps in the process caused by a misfit between norms of the process participants. We present a rationale for the anticipation and resolution of these misfits. We extend the traditional operational model with an appreciative model. This model represents the appreciative systems of process participants. Understanding these appreciative systems is necessary to make explicit the misfit between the model and the observed reality. The operational model represents the “technical” perspective on the business process, the one that can be automated. The appreciative model represents the “social” perspective, the one that explains the participants’ behavior as a result of their individual and collective norms. By combining these two perspectives, we can appreciate the richness of the development of socio-technical systems.